Pengaruh Penerapan Model Pembelajaran TREFFINGER terhadap Hasil Belajar Siswa pada Materi Kesetimbangan Kimia (Milenial: Journal for Teachers and Learning, 2021)
This research was instigated by the low of student learning achievement on Chemical Equilibrium lesson. It was a quasi-experiment research with pretest and posttest design. It aimed at knowing the effect of implementing TREFFINGER learning model toward student learning achievement on Chemical Equilibrium lesson at the eleventh grade of Natural Science at Islamic Senior High School of Al Ihsan Boarding School Pekanbaru. Simple random sampling technique was used in this research, and there were two sample classes—the eleventh-grade students of Al Farabi were as the control group and the students of Al Kindi were as the experimental group. The techniques of collecting the data were test in the forms of homogeneity test as the preliminary data, pretest and posttest as the final data, and documentation. The learning achievement data then were analyzed by using t-test with 0.05 level. The research findings showed that there was an effect of implementing TREFFINGER learning model toward student learning achievement on Chemical Equilibrium lesson at the eleventh grade of Natural Science at Islamic Senior High School of Al Ihsan Boarding School Pekanbaru. The score of tobserved was 2.08 and ttable was 1.99 at 0.05 significant level, tobserved was higher than ttable, so Ha was accepted and H0 was rejected, and the coefficient of effect was 7%.